Inventory Inventarisasi Emisi Karbon Dioksida (CO₂) dan Analisis Kecukupan Ruang Terbuka Hijau (RTH) di Kecamatan Lamongan berdasarkan NDVI - Aldi Andrianto; Muhammad Abdus Salam Jawwad (Racic : Rab Construction Research, 2026)
Climate change has become a global issue receiving serious attention worldwide. One of its principal drivers is the increase in Greenhouse Gases (GHG), particularly carbon dioxide (CO₂). Therefore, effective spatial-planning–based mitigation strategies are required. This study aims to analyze the capacity of Green Open Space (RTH) to absorb CO₂ emissions in Lamongan Subdistrict. The methods include Sentinel-2 satellite imagery analysis using the NDVI (Normalized Difference Vegetation Index) approach to determine vegetation cover, combined with carbon stock calculations based on IPCC (2006) guidelines. In addition, CO₂ emissions were inventoried from the transportation sector, household energy use (LPG), electricity, and domestic solid and liquid waste using the IPCC Tier-1 approach. The results show that the total estimated CO₂ emissions in Lamongan Subdistrict reach 17.927,46 tons/year. Meanwhile, the absorption capacity of existing RTH can absorb approximately 5.686 tCO₂/year, or 32% of total emissions, leaving residual emissions unabsorbed.